ВПЛИВ ЧИСЛА ФАЗ ОБМОТКИ ОБЕРТАННЯ НА СТРУКТУРУ ТА ВЛАСТИВОСТІ ЕЛЕКТРИЧНОЇ МАШИНИ З ТРИСТУПЕНЕВИМ РОТОРОМ - Пєтухов, І.С.; Кірєєв, В.Г.; Акинін, К.П.; Лавриненко, В.А. (Інститут електродинаміки НАН України, Київ, 2023)
The structure of an electric machine with a rotor, which has three degrees of freedom of rotation (EMTR) and consists of external and internal magnetic circuits, is considered. Between them, in the air gap of a spherical configuration, there is an m-phase rotation winding and a control winding. The excitation of the magnetic field in the EMTR is carried out by means of permanent magnets located on the external magnetic circuit. The scope of application of EMTP in systems of stabilization, observation, tracking, where the rotor performs the function of a gyro-stabilizing element, is outlined. Taking into account the structure of the considered EMTR, the absence of eddy currents in the design and the suitability of the mathematical model of the static magnetic field are substantiated. The calculation of the torque of the EMTR with two- and three-phase rotational windings at different angles of rotor’s inclination relative to the stator axis has been performed. It is shown that the rotation torque of the three-phase winding is 20% higher than that of the two-phase winding. A significant influence of the control winding on the torque of the three-phase winding and approximately the same influence of the two- and three-phase rotation windings on the processional torque with a significant value of the rotor inclination angle are noted. References 7, figures 8, tables 1.